2020
DOI: 10.1101/2020.01.19.911149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compartmentalization of enhanced biomolecular interactions for high-throughput drug screening in test tubes

Abstract: Modification-dependent and -independent biomolecular interactions (BIs), including protein-protein, protein-DNA/RNA and protein-lipid, play crucial roles in all cellular processes. Dysregulation of BIs or malfunction of the associated enzymes results in various diseases, thus they are attractive targets for therapies. High-throughput screening (HTS) can greatly facilitate the discovery of drugs for these targets. Here we describe a HTS drug discovery method, called compartmentalization of enhanced biomolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Image analysis of heterogeneity of the fluorescence intensity and quantification of the cells with condensates indicated that almost all the combinations of interacting pairs induce formation of biological condensates, except the combination of TFAM1 and TFAM2, whose interaction displays homogenous fluorescence signals ( Figure 6A, 6B and Supplemental Figure 3). To validate the interactions in vitro and monitor the phase separation behavior during interactions without disturbance from other potentially interacting partners, we recombinantly expressed and purified mCherry-TMF (red fluorescence) and GFP-TFAM (green fluorescence) proteins to perform crossmixing phase separation reactions (Zhou et al, 2020). Apparently, TMF can coexist with itself to form the perfectly merged droplets ( Figure 6C).…”
Section: Tmf Selectively Recruits Tfams Into Phase Separated Condensatesmentioning
confidence: 99%
“…Image analysis of heterogeneity of the fluorescence intensity and quantification of the cells with condensates indicated that almost all the combinations of interacting pairs induce formation of biological condensates, except the combination of TFAM1 and TFAM2, whose interaction displays homogenous fluorescence signals ( Figure 6A, 6B and Supplemental Figure 3). To validate the interactions in vitro and monitor the phase separation behavior during interactions without disturbance from other potentially interacting partners, we recombinantly expressed and purified mCherry-TMF (red fluorescence) and GFP-TFAM (green fluorescence) proteins to perform crossmixing phase separation reactions (Zhou et al, 2020). Apparently, TMF can coexist with itself to form the perfectly merged droplets ( Figure 6C).…”
Section: Tmf Selectively Recruits Tfams Into Phase Separated Condensatesmentioning
confidence: 99%